2005
DOI: 10.1007/bf03373236
|View full text |Cite
|
Sign up to set email alerts
|

Mehr institutioneller Wettbewerb in Deutschland -Wirksame Hilfe für die neuen Bundesländer

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Before reunification in 1990, it was part of the German Democratic Republic. Studies have shown that Brandenburg is stagnating at a low level with respect to R&D activities, patent applications, competitiveness and economic growth [45][46][47]. The district of Märkisch-Oderland (MOL) within this state is located east of Berlin and borders Poland to the east.…”
Section: Model Region Märkisch-oderland Districtmentioning
confidence: 99%
“…Before reunification in 1990, it was part of the German Democratic Republic. Studies have shown that Brandenburg is stagnating at a low level with respect to R&D activities, patent applications, competitiveness and economic growth [45][46][47]. The district of Märkisch-Oderland (MOL) within this state is located east of Berlin and borders Poland to the east.…”
Section: Model Region Märkisch-oderland Districtmentioning
confidence: 99%